Community-Based Tourism in Kresek Village, Madiun, East Java - Yudi Hartono; Bambang Soemardiono; Soebijantoro Soebijantoro (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2021)
Purpose: This research aims to reveal the role of community in tourism development and formulate community-based tourism in historical tourism areas of Kresek Monument in Kresek Village, Wungu District, Madiun Regency, East Java. Research methods: This research is carried out with a qualitative explorative method. Data was collected through in-depth interviews, observations, Focus Group Discussions, and the study of documentation. Data validity was obtained through source triangulation. Data analysis with interactive analysis model. Results and discussions: The result shows that the people succeeded to transform historical trauma into tourism potential through various recreational and educational activities, but the absence of synergy of policies among the stakeholders becomes a hindrance in developing the historical tourism area. Through a series of Focus Group Discussions, the model of Community-Based Tourism (CBT) was formulated for the empowerment of people in developing tourism in the historical tourism areas in Kresek Village. The community is actively involved in the selection, planning, and evaluation the tourism development. These models can be implemented in rural tourism development. The result of implementation models can contribute to the improvement of the economy and standards of living in the local community, the sustainability of tourism, and environmental conservation. Conclusion: The result of the implementation model can contribute to the improvement of economic standards of living in the local community, the sustainability of tourism, and environmental conservation.